Zakat-Based Socioprenuer Training for Tempe Entrepreneurship Communities - Saipul Wakit; Indra Irjani Dewijanti; Muhammad Mujtaba Mitra Zuana; Margiono Suyitno; Mekar Meilisa Amalia; Dewa Oka Supartawa (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
One of the programs that can respond to accelerated economic growth is economic activity that is linked to social problems (solopreneurship). This step is an effort in which crisis problems in society need to be anticipated and resolved together so that people who are weak in the economic sector can be helped and empowered based on equality and justice. this becomes important because, in the economic sector which is profitable in being managed, it becomes the basis of social religious power. because in the Islamic context, there is an economic concept that leads to a socio-religious nature through the zakat system. this is a solution in the case of an economic crisis in society. The principle of this economy is to promote a weak economy so that it grows and develops through a system of mutual assistance with sincerity and awareness of the principles of prosperity, equality, and justice. This activity was carried out for Tempe entrepreneurs so that they have a strong base as a group that concentrates on making Tempeh. The activity method is carried out through several stages, namely preparation, assessment, planning, and implementation. As for the results of this activity, there are groups/associations, administrators, secretariats for Tempe industry players, an increase in organizational and solopreneur knowledge as well as assistance and monitoring activities for program sustainability at partner locations